Synthesis, Catalytic Activity and Comparative Leaching Studies of Calix[8]arene‐Supported Pd‐NHC Complexes for Suzuki‐Miyaura Cross‐Couplings. Issue 5 (25th January 2022) - Abi Fayssal, Sandra; Naret, Timothée; Buendia, Julien; Labattut, Axel; Huc, Vincent; Martini, Cyril; Schulz, Emmanuelle
Abstract: A rapid and scalable synthesis of supported NHC−Pd(II)‐pyridine complexes on a benzyloxycalix[8]arene macrocycle is reported. Their subsequent use in Suzuki‐Miyaura benchmark reactions led to the optimisation of the nature of the ligands around the metal centre, delivering two very active precatalysts. They both promote the cross‐coupling of challenging API precursors at low catalytic loadings, when used as insoluble species in EtOH as a green reaction solvent. Moreover, their activity has been shown to be comparable or even superior to that of more conventional homogeneous catalysts. Of main importance, a simple filtration of the insoluble supported catalysts after reaction afforded the lowest Pd contamination values in the target products, in some cases directly approaching the levels authorised by the industrial regulations. Offering furthermore the possibility of easy palladium recovery in the current context of its overconsumption, we are convinced that these calixarene‐supported NHC‐PEPPSI Pd complexes are valuable tools for the fine chemical industry, to prepare metal‐free functionalised biaryl compounds in high yields, ranging from 76 to 94%. Abstract :